Silver-based nanomaterials: A critical review on factors affecting water disinfection performance and silver release. Issue 20 (27th August 2021) - Bahcelioglu, Ecem; Unalan, Husnu Emrah; Erguder, Tuba Hande
Abstract: Water safety is one of the major environmental issues. Drawbacks of the conventional disinfection methods necessitate alternative, novel, low-cost, safe and highly efficient disinfection methods. With the advancements in nanotechnology, excellent antibacterial properties of nanosilver started to be used extensively in disinfecting medical devices, food packaging, clothing-fabrics and water-air disinfection. Recent studies showed that nanosilver-based materials used as disinfectants are highly promising to replace or to enhance the effectiveness of the conventional water disinfection methods. This is because, nanosilver-based materials do not generate carcinogenic disinfection-by-products (DBPs), require less energy, have no clogging problem, and achieve high removal efficiencies. In order to develop and improve disinfection methods with nanosilver-based materials, it is fundamental to understand the factors affecting their water disinfection performance. This review article, for the first time, focuses on the major factors affecting the water disinfection performance of nanosilver-based materials such as microbial culture, flow rate, silver concentration and water characteristics. The factors affecting silver release were also discussed. Understanding of these factors would certainly improve the development of nanosilver-based technologies. The compilation of the results presented herein will be helpful in guiding researchers who aim to work on this subject. Graphical Abstract: UF0001